Tandem catalysis by in-situ generated microporous COF-Pd nanoparticle hybrids - Bhadra, Mohitosh; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: covalent organic frameworks; Pd nanoparticles; tandem catalysis

Mechanochemically synthesized covalent organic framework as a proton-conducting solid electrolyte - Shinde, Digambar Balaji; Aiyappa, Harshitha Barike; Bhadra, Mohitosh; Biswal, Bishnu P.; Wadge, Pritish; Kandambeth, Sharath; Garai, Bikash; Kundu, Tanay; Kurungot, Sreekumar; Banerjee, Rahul (Journal of Materials Chemistry A, 2016)
Mechanochemistry has become an increasingly important synthetic tool for a waste-free environment. However, the poor quality of the so-derived materials in terms of their crystallinity and porosity has been their major drawback for any practical applications. In this report, we have for the first time successfully leveraged such characteristics to show that the mechanochemically synthesized bipyridine based covalent organic framework (COF) outperforms its conventional solvothermal counterpart as an efficient solid-state electrolyte in PEM fuel cells. Marking the first such attempt in COFs, a Membrane Electrode Assembly (MEA) fabricated using the mechanochemically synthesized COF was observed to inhibit the fuel crossover and build up a stable Open Circuit Voltage (OCV = 0.93 V at 50 degrees C), thereby establishing itself as an effective solid electrolyte material (with a proton conductivity of 1.4 x 10(-2) S cm(-1)), while the solvothermally synthesized COF proved ineffective under similar conditions.

Predesigned metal-anchored building block for in situ generation of Pd nanoparticles in porous covalent organic framework: application in heterogeneous tandem catalysis - Bhadra, Mohitosh; Sasmal, Himadri Sekhar; Basu, Arghya; Midya, Siba P.; Kandambeth, Sharath; Pachfule, Pradip; Balaraman, Ekambaram; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2017)
The development of nanoparticle-polymer-hybrid-based heterogeneous catalysts with high reactivity and good recyclability is highly desired for their applications in the chemical and pharmaceutical industries: Herein, we have developed a novel synthetic strategy by choosing a predesigned metal-anchored building block for in situ generation of metal (Pd) nanoparticles in the stable, porous, and crystalline covalent organic framework (COF), without using conventional reducing agents. In situ generation of Pd nanoparticles in the COF Skeleton is explicitly confirmed' from PXRD, XPS, TEM images, and N-15 NMR spectral analysis. This hybrid material is found to be an excellent reusable heterogeneous catalyst for the synthesis of biologically and pharmaceutically important 2-substituted benzofurans from 2-bromophencils and terminal alkynes via a tandem process with the turnover number up to 1101. The heterogeneity of the catalytic process is unambiguously verified by a mercury poisoning experiment and leaching test. This hybrid material shows superior catalytic performance compared to commercially available homogeneous as well as heterogeneous Pd catalysts.

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Triazine functionalized porous covalent organic framework for photo-organocatalytic E-Z isomerization of olefins - Bhadra, Mohitosh; Kandambeth, Sharath; Sahoo, Manoj K.; Addicoat, Matthew; Balaraman, Ekambaram; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Visible light-mediated photocatalytic organic transformation has drawn significant attention as an alternative process for replacing thermal reactions. Although precious metal/organic dyes based homogeneous photocatalysts have been developed, their toxic and nonreusable nature makes them inappropriate for large-scale production. Therefore, we have synthesized a triazine and a keto functionalized nonmetal based covalent organic framework (TpTt) for heterogeneous photo catalysis. As the catalyst shows significant absorption of visible light, it has been applied for the photocatalytic uphill conversion of trans-stilbene to cis-stilbene in the presence of blue light-emitting diodes with broad substrate scope via an energy transfer process.